Correlation of epiploic foramen length to height, weight, breed, gender and age in horses - Alonso, J. M.; Rosa, G. S.; Marsiglia, M. F.; Garcia Alves, A. L.; Rodrigues, C. A.; Watanabe, M. J.; Figueiredo Pantoja, J. C.; Hussni, C. A. (Wiley, 2018)
Epiploic foramen entrapment (EFE) is one of the most common causes of small intestinal strangulation in horses. Cribbing and previous episodes of colic are suggested as risk factors for its occurrence. The aim of this study was to correlate the height, weight, breed, gender and age to the epiploic foramen (EF) length. Forty-three horses were submitted to post-mortem measurement of epiploic foramen with abdominal and thoracic organs positioned in situ. After data collection, linear regression between EF length and the explanatory variables was performed. None of the post-mortem physical variables was associated with EF length, supporting the hypothesis that there is no association between EF length and age, and that increased intra-abdominal pressure is the most important factor predisposing to EFE recurrence.
Keywords: Colic; Cribbing; Horse; Small intestine strangulation; Winslow foramen